Extracting Inflation from Stock Returns to Test Purchasing Power Parity - Chowdhry, Bhagwan; Roll, Richard; Xia, Yihong (American Economic Review, 2005)
Relative purchasing power parity (PPP) holds for pure price inflations, which affect prices of all goods and services by the same proportion, while leaving relative prices unchanged. Pure price inflations also affect nominal returns of all traded financial assets by exactly the same amount. Recognizing that relative PPP may not hold for the official inflation data constructed from commodity price indices because of relative price changes and other frictions that cause prices to be “sticky,” we provide a novel method for extracting a proxy for realized pure price inflation from stock returns. We find strong support for relative PPP in the short run using the extracted inflation measures.